Facile Preparation of Magnetic Porous Carbon Composites from Sugarcane Bagasse via Simultaneous Magnetization and Activation and Their Use in Adsorption - Sirinad Mahawong (Prince of Songkla University, 2024)
Master of Science (Chemistry (Internatonal program)), 2019